Kontribusi Komponen Pendapatan Asli Daerah (PAD) Terhadap Realisasi PAD Kabupaten Lamongan Tahun 2020-2024 - Elsa Wahyu Pertiwi; Silvi Rahma Dhani Khoirunnisa; Eva Hany Fanida; Revienda Anita Fitrie (CV. ITTC INDONESIA, 2026)
Regional Original Revenue (PAD) is a key indicator in assessing the fiscal independence of a region. However, the contribution of each PAD component to total PAD realization tends to fluctuate and has not yet reached optimal levels, making it necessary to conduct an analysis to identify the most dominant components and observe their contribution trends over time. This study aims to examine the contribution of PAD components to the realization of PAD in Lamongan Regency during the period 2020–2024. This research employs a quantitative approach with a descriptive method. The data used are secondary data obtained from the Regional Revenue and Expenditure Budget (APBD) realization reports of Lamongan Regency. The data analysis technique involves calculating the percentage contribution of each PAD component, including local taxes, regional retributions, returns from separated regional assets, and other legitimate PAD, to the total PAD realization. The results indicate that the contribution of each PAD component changes from year to year. Other legitimate PAD contributes the largest share with an average of 52.69%, followed by local taxes at 28.49%, regional retributions at 15.42%, and returns from separated regional assets at 3.41%. In addition, the average contribution of PAD to total regional revenue is 17.61%, indicating that the fiscal independence of Lamongan Regency is still categorized as very low.